KESALAHAN BERBAHASA PADA KARANGAN EKSPOSISI SISWA SEKOLAH MENENGAH ATAS: BENTUK, FAKTOR PENYEBAB, DAN UPAYA MENGATASI - Utari Kismawati; Sumarwati Sumarwati; Nugraheni Eko Wardhani (Universitas Sebelas Maret, 2018)
The research population was all tenth grade Social students of Sekolah Menengah Atas Negeri 6 Surakarta. The research method used was qualitative method using descriptive-qualitative approach. The participants of the research were one hundred thirty (130) Social students’ works. The sampling technique used was purposive sampling. Data collection techniques were content analysis and in-depth interviewing. Data analyzing used was interactive analysis model. The followings are the conclusions of the research. First, three types of language errors in students’ exposition text are sentence error, diction error, and spelling error. Second, the most detected type of error is spelling error in which the use of comma has the highest percentage. Third, the casual factors of language error were as follow: the students know less about writing principles; the students have less motivation to read; the students tend to emphasize the idea rather than writing principle; the students tend to be lazy to do editing before submitting their works; the class condition is not supportive; and the students are demanded to write structurally correct. Fourth, some efforts done to minimize language error: teachers give clarification immediately when they notice language error; cross-reading among students before submitting their works; and more writing activities in class.